1992
DOI: 10.1080/09593339209385247
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in small, mammals

Abstract: Acute arsenic poisoning had been reported since the nineteenth century from smelting and refining activities. Many of these studies show that arsenic accumulated in the animals is not to concentration greater than 1 ug.g -1 . This study shows low levels of arsenic in the tissues of small mammals. For all four species of small mammals analysed; Sorex araneus, Clethrionomys glareolus, Microtus agrestis, and Apodemus sylvaticus showed that arsenic concentration in the spleen was higher than in bone followed by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Also presented is the rst use of MAS di usion-weighted spectroscopy as a tool to monitor necrosis in intact tissue. Tissue damage in the vole was not detected in the wood mouse (Apodemus sylvaticus), another rodent commonly found on contaminated sites (Ismail and Roberts 1992, Erry et al 1999, 2000, suggesting that renal tissue from the bank vole may be particularly susceptible to As 3 ‡ -induced damage. Male voles (20 : 6 § 0 : 9 (SE) g body weight, nˆ10) were divided randomly into two groups of ve.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also presented is the rst use of MAS di usion-weighted spectroscopy as a tool to monitor necrosis in intact tissue. Tissue damage in the vole was not detected in the wood mouse (Apodemus sylvaticus), another rodent commonly found on contaminated sites (Ismail and Roberts 1992, Erry et al 1999, 2000, suggesting that renal tissue from the bank vole may be particularly susceptible to As 3 ‡ -induced damage. Male voles (20 : 6 § 0 : 9 (SE) g body weight, nˆ10) were divided randomly into two groups of ve.…”
Section: Introductionmentioning
confidence: 97%
“…6, 377-385 Whereas most toxicology studies have involved laboratory animals, we are currently investigating the impact of environmental toxins on wild mammals (Gri n et al 2000a). Here, HRMAS 1 H-NMR was used to study the renal tissue of the bank vole (Clethrionomys glareolus), a species that commonly occurs on arsenic-contaminated sites (Ismail and Roberts 1992, Erry et al 1999, 2000, and the e ects that an environmentally realistic oral exposure to As 3 ‡ has on the kidney. As 3 ‡ is readily transported by erythrocytes with renal tissue being one of the initial target organs of this toxin (Oehme 1972).…”
Section: Introductionmentioning
confidence: 99%
“…The present results are particularly interesting, because the chosen ecological receptor was naturally exposed to arsenic contamination in the field rather than in a laboratory setting. Deer mice ( Peromyscus maniculatus ) were chosen as the ecological receptor, because they are excellent biomonitors of ecological health [6,7], have been used extensively in ERA [8–10], and as a result of their herbivorous habits, have direct contact with both soil and plant matter. Furthermore, the observations in Yellowknife of apparently healthy deer mice inhabiting mine tailings where arsenic levels are, in some cases, greater than 4,000 μg/g (a level that should pose adverse health effects based on traditional ERA calculations; C. Hough.…”
Section: Introductionmentioning
confidence: 99%
“…The effluents that directly come from the tannery industry go directly to the sewage system and thus contaminate the environment. It is observed that the concentrations of As in the soil and sediment of the investigated areas of Bangladesh are very high compared to the uncontaminated soils of the different countries of the world (Shacklette and Boerngen 1984;Sadler et al 1994;Nakadaira et al 1995;Temple et al 1977;Amonoo-Neizer et al 1988;Ismael and Roberts 1992;Harako 1986;Chutke et al 1995;Merry et al 1983;Chang et al 1999;Steinne et al 1989;Esser 1996;Sanok et al 1995;Merwin et al 1994; Table 4). The concentrations of As in the investigated foodstuffs collected from the Comilla district are very high as quoted in Table 4.…”
Section: Resultsmentioning
confidence: 99%